Optimalisasi Pembentukan Karakter Anak Usia Dini: Manajemen Kurikulum dengan Pendekatan Perenialis dan Motivasi Orang Tua di Sekolah Alam - Mauliyah, Anita; Naily Rohmah (Kiddo: Jurnal Pendidikan Islam Anak Usia Dini, 2024)
Having children who grow up with strong characters is the hope of parents when choosing their children to start formal education. Early childhood education institutions (PAUD), with their various creative efforts also carry out development and innovation to achieve the expected output targets for parents who entrust their children to study in PAUD/TK so that later children are more prepared to enter further education and have good personality characteristics. This study took a sample of students from PAUD/TK with a perennialist curriculum, a general PAUD curriculum, and a religion-based curriculum. This real experimental research uses a cross sectional approach - one shot design involving a comparison group of students from public schools and religion-based schools, with the aim of testing the perennialist curriculum management on outputs. Sampling of the experimental and control groups was taken from TK A, TK B, and graduates who were in elementary school 4th grade (aged 9-10) years. The results of the hypothesis test show that there is a strengthening of character from Kindergarten A to Kindergarten B and SD Grade 4, where children can maintain the values ​​that are embedded while studying in PAUD/TK. The results of study also prove that there is a correlation between parents' motivation to send their children to school and parents' expectations of educational outcomes, which is indicated by differences in attitudes and behavior of children from PAUD/TK. Children with perennialist-based learning can show behavior of honesty, courage (brainly), cohesiveness, be helpful (mutual help) which is relatively stable, and show leadership (leadership) that stands out in class when sitting in education. base. Curriculum management with a perennialist approach is proven to foster values, self-efficacy and children's adversity quotient.